Delayed, recurrent bile leak from isolated right posterior sectoral duct injury after laparoscopic cholecystectomy: An unusual presentation. Issue 7 (18th July 2022) - Sharma, Amit; Ruch, Brianna; Alwatari, Yahya; Lele, Sonia; Bouhaidar, Doumit S.
Abstract: Bile leak after cholecystectomy is associated with significant comorbidity. Biliary duct variant anatomy can complicate identification and management. We report a very rare presentation of recurrent delayed bile leaks years after laparoscopic cholecystectomy secondary to missed right posterior sectoral bile duct injury. Surgical intervention was required after the failure of conservative management. Abstract : Right posterior sectoral duct injury should be considered in patients presenting with a delayed recurrent bile leak. Deep dissection into liver parenchyma during gallbladder fossa dissection should be avoided to prevent the occurrence of such injuries.